The Influence of Detergents on the Physical and Mechanical Properties of Clothing Fabrics - Muhammad 'Izzat Zainul Abidin; Nur Azam Badarulzaman (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Cotton textiles have found wide application in both male and female clothing due to its comfort attributes. It happens to be the most commonly used natural fibre in the world today. But it was found drawbacks for this fabric after the cleaning process is done. The reason for this is because the washing condition, detergent type, and drying condition are all key factors that determine the level of damage. The main objective of this study is to study the influence of commercial laundry detergent on cotton fabrics by carrying out the shrinkage, tensile strength, and tearing strength test. The method that was used for this test is using AATCC test method 135-2004 related to ISO 3759 which dimensional changes of fabrics after home laundering with different amounts of detergents. A washing machine with top loading is used to clean the fabric. The detergent used for this study is in powder and liquid form. These two types of detergents have different approaches toward fabric. All the laundering processes are done with the same washing condition. The experiment was divided into two parts, where measurement was carried out to examine the properties of textile material before the detergent treatment and after the detergent treatment. Then, the fabric characteristics before and after the detergent treatment are determined. According to the result obtained, liquid have tendency to make fabric changed in fabric structure whereby can reduce the fabric strength compared to powder detergent. Due to the concentration of the detergent, the fabric also experiences a decrease in strength. The overall shrinkage test showed a decrease in fabric dimensions after laundering which is in between 2 to 5 percent. The detergent treatment caused the greatest loss of breaking strength for both types of detergents whereby it loss in between 5 to 48 percent. The loss of strength also happened to tearing strength where it loss in between 8 to 44 percent.